(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Polluted air is a combination of particles and gases that can accumulate to unhealthy levelsinside and out. Its effects may include, but are not limited to, higher temperatures and an elevated risk ofdisease. To name only a few examples of common contaminants soot, smoke, mildew, pollen, methane,and carbon dioxide. Air pollution has been linked to cellular oxidative stress and inflammation, whichmay provide the foundation for chronic diseases and cancer in humans. When these fuels are used,they release greenhouse gases including carbon dioxide, methane, and nitrous oxide, all of which addto the problem of climate change. The loss of forest cover also has a role in the global warming. TheEarth’s environment is under continual danger due to global warming. Most individuals do not knowmuch about global warming and therefore do not think it will be a serious issue in the near future.Unfortunately, the effects of global warming are already being felt, although most people are unaware ofthis. Absolutely, and it will throw natural processes out of whack. The potentially disastrous effects ofglobal warming need the development of effective countermeasures.